Development of Antibody-Modified Nanobubbles Using Fc-Region-Binding Polypeptides for Ultrasound Imaging - Nobuhito Hamano; Sho Kamoshida; Yamato Kikkawa; Yusuke Yano; Tomomi Kobayashi; Yoko Endo-Takahashi; Ryo Suzuki; Kazuo Maruyama; Yuji Ito; Motoyoshi Nomizu; Yoichi Negishi (MDPI AG, 2019)
Ultrasound (US) imaging is a widely used imaging technique. The use of US contrast agents such as microbubbles, which consist of phospholipids and are filled with perfluorocarbon gases, has become an indispensable component of clinical US imaging, while molecular US imaging has recently attracted significant attention in combination with efficient diagnostics. The avidin−biotin interaction method is frequently used to tether antibodies to microbubbles, leading to the development of a molecular targeting US imaging agent. However, avidin still has limitations such as immunogenicity. We previously reported that lipid-based nanobubbles (NBs) containing perfluorocarbon gas are suitable for US imaging and gene delivery. In this paper, we report on the development of a novel antibody modification method for NBs using Fc-region-binding polypeptides derived from protein A/G. First, we prepared anti-CD146 antibody-modified NBs using this polypeptide, resulting in high levels of attachment to human umbilical vein endothelial cells expressing CD146. To examine their targeting ability and US imaging capability, the NBs were administered to tumor-bearing mice. The contrast imaging of antibody-modified NBs was shown to be prolonged compared with that of non-labeled NBs. Thus, this antibody modification method using an Fc-binding polypeptide may be a feasible tool for developing a next-generation antibody-modified US imaging agent.